Identification of the LOX Gene Family in Peanut and Functional Characterization of AhLOX29 in Drought Tolerance - Mou, Yifei; Sun, Quanxi; Yuan, Cuiling; Zhao, Xiaobo; Wang, Juan; Yan, Caixia; Li, Chunjuan; Shan, Shihua (Frontiers in Plant Science, 2022)
Lipoxygenases (LOXs) are a gene family of nonheme iron-containing dioxygenases that play important roles in plant development and defense responses. To date, a comprehensive, systematic analysis of LOX genes and their biological functions in response to abiotic stresses in peanut has not been performed. In this study, a total of 72 putative LOX genes were identified in cultivated (Arachis hypogaea) and wild-type peanut (Arachis duranensis and Arachis ipaensis) and classified into three subfamilies: 9-LOX, type Ⅰ 13-LOX and type Ⅱ 13-LOX. The gene structures and protein motifs of these peanut LOX genes were highly conserved among most LOXs. We found that the chromosomal distribution of peanut LOXs was not random and that gene duplication played a crucial role in the expansion of the LOX gene family. Cis-acting elements related to development, hormones and biotic and abiotic stresses were identified in the promoters of peanut LOX genes. The expression patterns of peanut LOX genes were tissue-specific and stress-inducible. Quantitative real-time PCR (qRT–PCR) results further confirmed that peanut LOX gene expression could be induced by drought, salt, MeJA and ABA treatments, and these genes exhibited diverse expression patterns. In addition, overexpression of AhLOX29 in Arabidopsis enhanced their resistance to drought stress. Compared with wild-type plants, overexpression plants showed significantly decreased MDA contents, and increased chlorophyll degradation, proline accumulation and SOD activity, suggesting the increased ability of transgenic plants to scavenge ROS and prevent membrane damage. Our systematic study of the LOX gene family provides valuable information about the functional characteristics of AhLOXs in the regulation of the abiotic stress responses of peanut.